Integrating a Parent-Implemented Blend of Developmental and Behavioral Intervention Strategies into Speech-Language Treatment for Toddlers at Risk for Autism Spectrum Disorder - Rieth, Sarah R.; Haine-Schlagel, Rachel; Burgeson, Marilee; Searcy, Karyn; Dickson, Kelsey S.; Stahmer, Aubyn C. (Seminars in Speech and Language, 2018)
Naturalistic developmental behavioral interventions include an explicit focus on coaching parents to use therapy techniques in daily routines and are considered best practice for young children with autism. Unfortunately, these approaches are not widely used in community settings, possibly due to the clinical expertise and training required. This article presents the work of the Bond, Regulate, Interact, Develop, Guide, Engage (BRIDGE Collaborative), a multidisciplinary group of service providers (including speech-language pathologists), parents, funding agency representatives, and researchers dedicated to improving the lives of young children with autism spectrum disorder and their families. The group selected and adapted a parent coaching naturalistic developmental behavioral intervention specifically for use with toddlers and their families for community implementation. Lessons learned from the implementation process include the importance of therapist background knowledge, the complexity of working with parents of young children, and needed supports for those working closely with parents, including specific engagement strategies and the incorporation of reflective practice.
Keywords: Naturalistic developmental behavioral intervention; parent coaching; early intervention; reflective practice